Geometric Registration of High Spatial Resolution Images Based on Google Earth Image and Global DEM Data - J. T. Zhang; X. XU; J. Zhang (Lowland Technology International, 2019)
application of remote sensing technology is expanding. Before the application of remote sensing images, geometric registration and other preprocessing are often required for tilt correction and projection error correction, which often requires the selection of ground control points. Given the lack of measured ground control points, the correction accuracy will be greatly limited. In this paper, a remote sensing image orthographic correction process based on Google earth and Global DEM is proposed. First, in ENVI5.3, the image to be corrected and the reference image (Google Earth image) were automatically matched with the corresponding ground object points to obtain the coordinate file of the correction control point (.pts), and the coordinates were converted to plane coordinates. Under the ArcGIS10.2 platform, the data of the coordinate table of the correction control points were converted into the ArcGIS point file (SHP). Finally, the point file was spatially superimposed with the elevation data of Global DEM to obtain the elevation value, and then the ground control point file with elevation value was obtained, and then the orthographic correction with control points was carried out. The result showed that compared with the orthophoto correction without control points, the processing process adopted in this paper can improve the accuracy of correction, and the accuracy can meet the requirements of the 1:10000 land survey in the working base map. This research is expected to provide a new method for obtaining high-quality digital orthophoto images needed for land surveys.